2011
DOI: 10.4067/s0716-97602011000200004
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine-Rich Secretory Proteins (CRISP) and their role in mammalian fertilization

Abstract: Epididymal protein CRISP1 is a member of the CRISP (Cysteine-RIch Secretory proteins) family and is involved in sperm-egg fusion through its interaction with complementary sites on the egg surface. Results from our laboratory have shown that this binding ability resides in a 12-amino-acid region corresponding to a highly conserved motif of the CRISP family, named Signature 2 (S2). In addition to this, our results revealed that CRISP1 could also be involved in the previous step of sperm binding to the zona pell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 25 publications
0
12
0
1
Order By: Relevance
“…The absence of testes-support cell-related proteins and the enrichment of exosomal proteins reinforces the notion of seminal fluid and spermatozoa communication through the exosomes released by the accessory sex glands. Whereas the majority of proteins related to the interaction of sperm with the zona pellucida are sperm-specific, e.g., IZUMO1 (Chalbi et al 2014), approximately one-quarter, e.g., zona pellucida binding protein (Lin et al 2007), heat shock-related 70-kDa protein 2 (Nixon et al 2015) and cysteine-rich secretory proteins 1 and 2 (reviewed in Cohen et al 2011), were identified in both sperm and seminal plasma proteomes. This suggests that some proteins that may play a role in sperm-egg recognition or interaction could be acquired externally from the seminal fluid.…”
Section: Human Semen Proteomementioning
confidence: 99%
“…The absence of testes-support cell-related proteins and the enrichment of exosomal proteins reinforces the notion of seminal fluid and spermatozoa communication through the exosomes released by the accessory sex glands. Whereas the majority of proteins related to the interaction of sperm with the zona pellucida are sperm-specific, e.g., IZUMO1 (Chalbi et al 2014), approximately one-quarter, e.g., zona pellucida binding protein (Lin et al 2007), heat shock-related 70-kDa protein 2 (Nixon et al 2015) and cysteine-rich secretory proteins 1 and 2 (reviewed in Cohen et al 2011), were identified in both sperm and seminal plasma proteomes. This suggests that some proteins that may play a role in sperm-egg recognition or interaction could be acquired externally from the seminal fluid.…”
Section: Human Semen Proteomementioning
confidence: 99%
“…CRISPs represent an extensive family of highly conserved cysteine-rich secretory proteins, comprising three main groups, named CRISP-1, CRISP-2 and CRISP-3 [8]. The main biological functions related to CRISP-1 and CRISP-2 include ion channels blocking and involvement in the processes of gametes maturation and fusion, being in this case mediated by a motif named signature 2 [9]. CRISP-3 is found in blood plasma and exocrine secretions and its role in…”
Section: Introductionmentioning
confidence: 99%
“…The cysteine-rich venom proteins (CRVPs) belong to the larger family of proteins known as the cysteine-rich secretory proteins (CRISPs), and are found in the venoms of diverse species, including snakes, cone snails, coleoids, stinging insects, scorpions and spiders [82][83][84][85][86][87][88] . Proteins from this family are also commonly found in the mammalian male reproductive tract 89 and are associated with a broad range of functions, such as fertilization and sperm-egg interaction 86,88 . In the current study, 8 transcripts that encode venom-like CRISPs were identified within the SG-AL, and 2 were confirmed through proteomic analysis ( Table 2).…”
Section: Resultsmentioning
confidence: 99%